Integrasi Pendidikan Lingkungan Dalam Pembelajaran Sains Untuk Mengembangkan Kesadaran Ekologis Pada Siswa Sekolah Dasar - Marlina Marlina; Irma Septiani Daffa; Nina Nina; Harlina Haris; Salmawati Salmawati (Prodi PGSD Unsultra, 2024)
Increasing ecological awareness from an early age is a strategic step in facing global environmental challenges. This article discusses the integration of environmental education in science learning in elementary schools as an approach to developing students' ecological awareness. Through interactive and project-based learning methods, students can understand the relationship between science and the environment. This study shows that this approach not only improves students' understanding of scientific concepts but also encourages them to take real action in protecting the environment.